Reflective Implementation of Tajweed Instruction to Enhance Quranic Reading Skills at Pondok Pesantren Nurul Hidayah Alal Ardhi - Hidayah, Ade Rahmatul; Kurniawan, Akhmad Kharis; Rizki, Reffy Ananda; Dewi, Retno Ayu Atikah; S, Sadarela (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to explore the implementation of tajweed instruction through talaqqi and halaqah methods in the natural educational setting of Pondok Pesantren Nurul Hidayah Alal Ardhi. Using a qualitative approach with a case study and document analysis design, the research investigates the instructional dynamics of Quranic reading practices. Data were collected through field observation, interviews, and documentation, and analyzed using Miles and Hubermans interactive model, which includes data reduction, data display, and conclusion drawing. The findings reveal that talaqqi and halaqah methods not only serve as tools to preserve traditional sanad-based Quranic education but also prove effective in improving students reading accuracy and understanding of tajweed. However, their effectiveness is influenced by learners initial abilities, the intensity of teacher guidance, and contextual implementation factors. While the methods are still widely favored, the study recommends the development of preparatory tajweed programs and enhanced teacher involvement to optimize outcomes. The success of tajweed instruction depends not only on tradition but also on its adaptability to learners real educational needs.